How Price and Product Quality Influence Customer Satisfaction: A Case Study of Retail Traders at Daya Wholesale Market - Dammar, Tria Haryuni; Yahya, Muhammad (Journal of Entrepreneur, Business and Management, 2024)
This study aims to find out the influence of price and product quality on consumer activity in Retail Traders of Daya Wholesale Market.The population in this study is as many as 100 respondents with a sample of 100 respondents. The sampling technique that was seeded was simple random sampling. The data analysis technique used is multiple regression analysis. Based on the results of the research and data analysis, the conclusion of this study is that price has a significant effect on consumer satisfaction who shop at retail traders at Pasar Grosir Daya stores as seen with a calculated t value of 1.545 and a significance value of 0.126 (below 0.005). Non-financial compensation has a significant effect on the satisfaction of consumers who shop at retail traders at Pasar Grosir Daya stores as seen with a t-value of 4,205 and a significance value of 0.000 (below 0.005). Simultaneously, price and product quality have a significant effect on consumer satisfaction who shop at retail traders at Pasar Grosir Daya stores, the R square value is 0.321, which means that price and product quality have an effect of 32.1% on consumer satisfaction who shop at retail traders at Pasar Grosir Daya stores.Keywords: Price, product quality, consumer satisfaction.